Cognitive behaviour therapy in non-western cultures :Malaysian and Bruneian perspective - Narasappa Kumaraswamy (Nova Science Publishers, Inc., 2012)
Cultural identity has a profound impact on our sense of well-being and our own mental and physical health within the context of our respective societies. While cultural background refers to our ethnicity, it is also the influence of our family, social class, religion, migration, geography, gender and sexual orientation that mold who we are as diverse human beings. Over the decades, many attempts have been made by proponents of various psychotherapeutic modalities to develop population - specific approaches for ethnic groups - only leading to fragmentation, confusion and controversy in the professional field. This new book presents and discusses current research in the study of CBT in non-western cultures.